IMPACT OF ECONOMIC GROWTH, INFLATION AND MINIMUM WAGE ON POVERTY IN JAVA - Joko Susanto (MEDIA, 2014)
This research analysis the impact of economic variable, which includes growth, inflation and minimum wage, on poverty rate in Java. Research coverage is poverty in Java because most of the poor live in this island. The secondary data that published by Indonesian Statistic is used in this research. This research used dynamic panel data regression based on Error Correction Model (ECM). The results show that the economic growth has negative impact on poverty rate in java, while the inflation has positive impact on poverty rate in Java. A higher economic growth is correspond to a lower poverty rate, while a higher inflation is correspond to a higher poverty rate. Furthermore, minimum wage has no impact on poverty rate in Java.